THE EFFECTIVENESS OF LAND AND BUILDING TAX REVENUE FROM CENTRAL TO REGIONAL TAXES AT THE PALEMBANG CITY REGIONAL REVENUE OFFICE - Hasyunah; Yasmina Martini (Jurnal Kompetitif, 2023)
Law Number 28 of 2009 limits the object of regional taxes and levies collected by local governments, including the delegation of Land and Building Tax management to the Rural and Urban sectors.  In this study, researchers want to know and analyze Land and Building Tax revenues from central to regional taxes at the Palembang City Regional Revenue Office. This study used comparative descriptive. The results of this study are as follows: first: the percentage of the target revenue of Land and Building Tax in the Rural and Urban sector of the Palembang City Regional Revenue Office in 2015 is 102.57% including very effective criteria. Second: obstacles that affect the level of effectiveness in Palembang City are differences in tax subject addresses, double printing occurs, human resource expertise is also still considered inadequate, the determination of tax objects that are not in accordance with the actual situation, taxpayer awareness and ability to pay taxes are not on time. Third: efforts to overcome obstacles that affect the level of effectiveness   of Land and Building Tax revenues, namely updating data or updating Land and Building Tax, distributing forms evenly to taxpayers, training human resources (employees of the Regional Revenue Office), coordination with the Land Agency for Land Zone Value.